Review of the millipede family Opisotretidae (Diplopoda, Polydesmida), with descriptions of new species - Golovatch, Sergei I. (Pensoft Publishers, 2013)
Abstract. The small, basically Oriental family Opisotretidae is rediagnosed, reclassified, and shown to comprise the following seven genera, all keyed: Carlotretus Hoffman, 1980, with two species, including Carlotretus triramus sp. n. from southern China; Corypholophus Attems, 1938, with two species, one in Vietnam, the other in the Ryukyus, Japan; Martensodesmus Golovatch, 1987, with eight species, all keyed, including Martensodesmus cattienensis sp. n. from southern Vietnam, as well as Martensodesmus bedosae sp. n. and Martensodesmus spiniger sp. n. from southern China; Opisotretus Attems, 1907, with seven species, all keyed, including Opisotretus beroni sp. n. and Opisotretus hagen sp. n., both from Papua New Guinea, Opisotretus deharvengi sp. n. from Sulawesi, Indonesia, and Opisotretus spinosus sp. n. from Nusakambangan Island, off Java, Indonesia; Opisthoporodesmus Silvestri, 1899, with six nominate species; Retrodesmus Chamberlin, 1945, with two species, i.e. the type-species Retrodesmus dammermani Chamberlin, 1945, from Java, Indonesia, revised from the holotype, and Retrodesmus cavernicola sp. n., from Papua New Guinea; and Solaenaulus Attems, 1940, with two species. Comments are presented on the family’s possible relationships and palaeogeographic history. Instead of being considered as the sole component of the superfamily Opisotretoidea, the Opisotretidae is believed here to form one of the families of the diverse superfamily Trichopolydesmoidea, perhaps the sister-group to, if not immediately derived from, the pantropical family Fuhrmannodesmidae. The origin of Opisotretidae, previously dated as far back as the Triassic (220 Ma) in relation to the fragmentation of eastern Gondwanaland, mainly in the region of present-day Indonesia, could have had nothing to do with Gondwanaland. Opisotretids might have originated in mainland Southeast Asia well within the Cenozoic, with subsequent dispersals along the Himalayas in the West and across Indonesia (including New Guinea) in the East, also reaching as far north as the Ryukyus, Japan and Guangxi, southern China.